Phomopsis longanae Chi-Induced Changes in Activities of Cell Wall-Degrading Enzymes and Contents of Cell Wall Components in Pericarp of Harvested Longan Fruit and Its Relation to Disease Development - Chen, Yihui; Zhang, Shen; Lin, Hetong; Sun, Junzheng; Lin, Yifen; Wang, Hui; Lin, Mengshi; Shi, John (Frontiers in Microbiology, 2018)
The main goal of this study was to investigate the influences of Phomopsis longanae Chi infection on activities of cell wall-degrading enzymes, and contents of cell wall components in pericarp of harvested “Fuyan” longan (Dimocarpus longan Lour. cv. Fuyan) fruit and its relation to disease development. The results showed that, compared with the control samples, P. longanae-inoculated longans showed higher fruit disease index, lower content of pericarp cell wall materials, as well as lower contents of pericarp cell wall components (chelate-soluble pectin, sodium carbonate-soluble pectin, hemicelluloses, and cellulose), but higher content of pericarp water-soluble pectin. In addition, the inoculation treatment with P. longanae significantly promoted the activities of cell wall-degrading enzymes including pectinesterase, polygalacturonase, β-galactosidase, and cellulase. The results suggested that the P. longanae stimulated-disease development of harvested longans was due to increase in activities of pericarp cell wall-degrading enzymes, which might accelerate the disassembly of pericarp cell wall components. In turn, resulting in the degradation of pericarp cell wall, reduction of pericarp mechanical strength, and subsequently leading to the breakdown of longan pericarp tissues. Eventually resulting in development of disease development and fruit decay in harvested longans during storage at 28 oC.